Effects of helium production, displacement damage on mechanical properties and surface acoustic wave in austenitic stainless steels and martensitic steel. (December 2018) - Wakai, E.; Kitazawa, S.; Takaya, S.; Okubo, N.; Nagae, Y.; Iwai, T.; Omata, T.; Abe, H.; Aoto, K.
Highlights: Effects of helium production, displacement damage on mechanical properties and surface acoustic wave (SAW) in austenitic stainless steels of 316FR and 304 and a martensitic steel HCM12A steels are presented. Large irradiation hardening due to He was measured by nano-indentation technique in 316FR, 304, and HCM12A irradiated at 550 °C in a high fluence irradiation facility (HIT). Correlation between the irradiation hardening and SAW propagation velocity was obtained in 316FR. SAW technique is very useful for irradiation damage as a non-destructive test. Abstract: The effects of helium production, displacement damage on mechanical properties and microstructures were investigated in some specimens such as austenitic stainless steels of SUS304 and SUS316 and a high chromium martensitic steel of HCM12A steels irradiated in a high fluence irradiation facility (HIT) of the University of Tokyo. The simultaneous dual ion (nickel plus helium ions) irradiations were adopted to simulate nuclear irradiation environments such as fast reactor and fusion reactor at HIT to 1 or 10 dpa and to 0, 1, 10, and 100 appm-He at 500, 550, and 600 °C. Thin foils for a transmission electron microscopy (TEM) were prepared with a focused ion beam (FIB) micro-sampling system. After the irradiation, the microstructures were observed by a transmission electron microscope and the irradiation hardening was measured by nano-indentation technique. In this study, the efficient of non-destructive measurement method of surface acoustic wave (SAW) excited by laser beam on the detection of radiation hardening behavior was also examined. Irradiation hardening was observed and the increment was tended to increase with dpa and He/dpa, which was especially effective in the condition of 100 appmHe/dpa even at 550 °C. Non-linear effect on amplitude of the excited SAW was also observed on the ion irradiated materials, and the propagation velocity of SAW was tended to be increased with irradiation dose. It was found that the behaviors of SAWs results were correlated with the changes of mechanical properties.